MONOCITOS DE LOS LEPROSOS I REVISTA CRITICA DE LA LITERATURA - GONZALEZ GUZMAN, IGNACIO (Instituto de Estudios Médicos y Biológicos, CD MEXICO, DF, MEX, 1945)
Adopting as a starting point the key elaborated by Hunter (1934), the author develops a practical method for the qualification of the high-school text-books adapted to the peculiarities of the Mexican habits and educational programs
BOL INST ESTUD MED BIOL
Keywords: MONOCITOS, LEPROSOS, REVISTA, CRITICA, LITERATURA; CIENCIAS MEDICAS; MEDICINA INTERNA; HEMATOLOGIA